NAUSICAA Compression Suture of The Lower Uterine Segment in Morbidly Adherent Placenta Previa Case - Arya Ady Nugroho; Sri Pudyastuti; Tri Apriliawan Bendarto Rahardjo (PT Dexa Medica, 2025)
Background: Placenta accreta spectrum or morbidly adherent placenta occurs mostly on a previous cesarean scar when placenta fails to detach due to abnormal invasion of placenta in to the uterine wall. The incidence of morbidly adherent placenta increased in the past decade from 0.8 per 1000 deliveries to 3 per 1000 deliveries.1 The increase in the incidence is attributed to increase in cesarean deliveries from 1 in about 2500 births to 1 in 500 births.2 A recent retrospective study reported that the rate of accreta for previous 1, 2, 3, 4, and 5 cesarean deliveries was found to be 26.7%, 43.5%, 65.5%, 55.6%, and 66.7%, respectively.3 Case presentation: In this study, We present a case of thirty-one year-old gravida III para II, 36 weeks of gestasional age, presented to the outpatient clinic and diagnosed with adhesive total placenta previa on US exam. Patient underwent c-section continued with nausicaa uterine compreesion suture, intraoperative bleeding was 1100 cc, there was no complication. Conclusion: Fertility-sparing surgery for women with morbidly adherent placenta could be one of the options to be considered. Nausicaa suture is a simple and feasible alternative to hysterectomy in patients suffering from major PPH.